The Ωc-puzzle solved by means of quark model predictions - Santopinto, Elena (2019)
The observation of five Ωc = ssc states by LHCb [Aaij et al. Phys. Rev. Lett. 118, 182001; (2017)] and the confirmation of four of them by Belle [Yelton et al. Phys. Rev. D 97, 051102; (2018)], may represent an important milestone in our understanding of the quark organization inside hadrons. By providing results for the spectrum of Ωc baryons and predictions for their Ξc⁺ K⁻ and Ξ'c⁺ K⁻ decay amplitudes within an harmonic oscillator based model, we suggest a possible solution to the Ωc quantum number puzzle and we extend our mass and decay width predictions to the Ωb states. Finally, we discuss why the set of Ωc(b) baryons is the most suitable environment to test the validity of three-quark and quark–diquark effective degrees of freedom.